Healing of soft tissue lacerations in diabetic‐induced rats. Issue 6 (17th October 2017) - Alzoubi, Fawaz; Joseph, Bobby; Andersson, Lars
Abstract: Background/Aim: Prevalence and incidence of diabetes are increasing and many dental trauma patients today have diabetes. The implications of delayed wound healing, associated with diabetes mellitus, on oral mucosal wound healing have not been investigated extensively. The aim of this study was to investigate the implications of diabetes mellitus on the cellular, vascular, and fibroblastic changes induced by laceration on the oral mucosa of Wistar rats. Materials and Methods: Sixteen female Wistar rats were randomly assigned into two groups: 1. Experimental Streptozotocin‐induced diabetic group (8 rats). 2. Control group (8 rats). A standardized laceration injury was induced from the corner of the mouth to the mid‐check penetrating through dermal and oral mucosal contaminated by saliva. Samples were taken from the rats after sacrificing them on days 1, 3, 7, and 10. Inflammation was evaluated both qualitatively and quantitatively. Two investigators evaluated samples in a blinded manner. Results: Histology reports indicated delayed wound healing patterns in diabetic rats through days 1, 3, 7, and 10 when compared to controls. Inflammation was also noted to be consistently present more often in diabetic rats. Furthermore, polymorphonuclear cell count was consistently higher in diabetic rats. Conclusion: The results suggest that oral mucosa wound healing is delayed in diabetic Wistar rats compared to non‐diabetic rats in terms of wound closure, angiogenesis, and polymorphonuclear cells number. Furthermore, it is also suggested that wound healing is impaired both in the early and late stages of soft tissue wound healing.